I spy spooky night : a book of picture riddles - Wick, Walter (New York : Scholastic, 1996)
Rhyming verses ask readers to find hidden objects in the photographs.
"Cartwheel books."
Keywords: Picture puzzles -- Juvenile literature; Riddles -- Juvenile literature; Puzzles -- Juvenile literature